Kepemimpinan Dalam Organisasi Atau Madrasah - Falah, Moh. Syamsul (MADINAH, 2014)
Leadership in organization or madrasah always interesting to be examined, considering the ability of a leader as main determinant of empowerment to subordinate. Leaders in the organization or madrasah as central to the success or failure of the organization or madrasah. For leaders in organizations or madrassas are required to be able to direct, influence, mobilize the bottom or kelomoknya in achieving the goals he has set. To achieve the goals of the organization or the madrasah would require its own steps, there are at least some urgent things to ponder by a leader in an organization or madrasah before managing its organization or madrasah, the leader on the basic concepts of leadership function, type of leadership, effective leadership, and leadership strategies or tactics. By understanding these things at least a leader is not only monotonous in leadership, so that his subordinates will experience saturation in the organization or madrasah which resulted in less effective and communicative people in the organization or madrasah.